IT Convergence and Security 2017 Volume 2 (Lecture Notes in Electrical Engineering,, 2018)
This is the second volume of proceedings including selected papers from the International Conference on IT Convergence and Security (ICITCS) 2017, presenting a snapshot of the latest issues encountered in the field. It explores how IT convergence and security issues are core to most current research, industrial and commercial activities and consists of contributions covering topics including machine learning & deep learning, communication and signal processing, computer vision and applications, future network technology, artificial intelligence and robotics. ICITCS 2017 is the latest in a series of highly successful Inter national Conferences on IT Convergence and Security, previously held in Prague, Czech Republic (2016), Kuala Lumpur, Malaysia (2015), Beijing, China (2014), Macau, China (2013), Pyeong Chang, Korea (2012), and Suwon, Korea (2011).